2018
DOI: 10.1017/s1041610218001618
|View full text |Cite
|
Sign up to set email alerts
|

A clinically-translatable machine learning algorithm for the prediction of Alzheimer’s disease conversion: further evidence of its accuracy via a transfer learning approach

Abstract: Background:In a previous study, we developed a highly performant and clinically-translatable machine learning algorithm for a prediction of three-year conversion to Alzheimer’s disease (AD) in subjects with Mild Cognitive Impairment (MCI) and Pre-mild Cognitive Impairment. Further tests are necessary to demonstrate its accuracy when applied to subjects not used in the original training process. In this study, we aimed to provide preliminary evidence of this via a transfer learning approach.Methods:We initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Moreover, the first principal component of the three ADAS scores, which resulted in the most individually important predictor, demonstrated a test AUROC significantly lower than the one achieved by the entire algorithm. The results of our, as well as other previous studies, had already showed that machine learning algorithms can effectively be used to combine these individual pieces of information, providing a better identification of cAD among MCI subjects than what it would be possible using each of them singularly [13,14,19,20,46] . 19 Our study has some limitations that should be taken into account and that will be addressed in the future stages of our research.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Moreover, the first principal component of the three ADAS scores, which resulted in the most individually important predictor, demonstrated a test AUROC significantly lower than the one achieved by the entire algorithm. The results of our, as well as other previous studies, had already showed that machine learning algorithms can effectively be used to combine these individual pieces of information, providing a better identification of cAD among MCI subjects than what it would be possible using each of them singularly [13,14,19,20,46] . 19 Our study has some limitations that should be taken into account and that will be addressed in the future stages of our research.…”
Section: Discussionmentioning
confidence: 52%
“…Nevertheless, the fact that our new algorithm does not necessitate any magnetic resonance evaluation makes its use even more easily translatable in practice, and less expensive. Moreover, even though our former algorithm showed higher cross-validated performance (AUROC = 0.91, sensitivity = 86.7% and specificity = 87.4% at the best balanced accuracy) [19] ), a solid testing of its performance is still lacking and, at the moment, only a preliminary evidence via a transfer learning approach is available [20] . Instead, the protocol applied in the current study provides a better and sounder evaluation of the actual predictive performance of this new algorithm.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations